Association between state payment parity policies and telehealth usage at community health centers during COVID-19. (21st July 2022) - Erikson, Clese; Herring, Jordan; Park, Yoon Hong; Luo, Qian; Burke, Guenevere
Abstract: Objective: We study the association between payment parity policies and telehealth utilization at community health centers (CHCs) before, during, and after the onset of the pandemic. Materials and Methods: We use aggregated, de-identified data from FAIR Health for privately insured patients at CHC sites. Descriptive statistics and time trends are calculated. Logistic regression models were used to quantify the factors associated with telehealth utilization for each of our time periods: 1) pre-pandemic (March-June 2019), 2) immediate pandemic response (March-June 2020), and 3) sustained pandemic response (March-June 2021). Results: Telehealth usage rates at CHC sites surged to approximately 61% in April 2020. By April 2021, only 29% of CHC sites in states without payment parity policies used telehealth versus 42% in states with payment parity policies. Controlling for other characteristics, we find that CHC sites in states with payment parity were more likely to utilize telehealth one year after the onset of the pandemic (OR:1.740, p<0.001) than states without, but did not find this association in 2019 or 2020. Discussion: The public health emergency drove widespread use of telehealth, making the virtual care environment inherently different in 2021 than in 2019. Due to the unique fiscal constraints facing CHCs, the financial sustainability of telehealth may be highly relevant to the relationship between telehealth utilization and payment parity we find in this paper. Conclusion: Supportive payment policy and continued investments in broadband availability in rural and undeserved communities should enable CHCs to offer telehealth services to populations in these areas.